Physiological characterization of Kluyveromyces marxianus strains for the development of a microbial platform to obtain bioethanol from cheese whey permeate - De Micco, Claudia; Radice, Matteo; Di Fidio, Nicola; Agrimi, Gennaro; Pisano, Isabella (Frontiers in Microbiology, 2025)
The increasing interest in renewable feedstocks for biochemicals production includes the valorization of cheese whey (CW), a by-product of the dairy industry. CW contains a high concentration of lactose, accounting for most of its organic load, making it a major environmental pollutant if untreated. A valorization approach of CW is based on the separation of valuable proteins by ultrafiltration, and the obtainment of a lactose-rich cheese whey permeate (CWP). The conversion of lactose in CWP into bioethanol is considered a sustainable solution for the valorization of this waste. However, lactose is not metabolized by the yeast species Saccharomyces cerevisiae, namely the most industrially used microorganism, to produce bioethanol. Differently, the non-conventional yeast Kluyveromyces marxianus shows high growth rates on a broad range of industrially relevant substrates, including lactose. This study provides a comprehensive physiological characterization of three K. marxianus strains (DSM 5422, DSM 7239, and DSM 5572) to evaluate their potential for lactose hydrolysis and fermentation in order to produce advanced bioethanol from CWP. Microplate growth tests, β-galactosidase activity assays, and flask fermentations were carried out to identify optimal strains for efficient CWP valorization, advancing the applications of K. marxianus in industrial biotechnology. The optimal conditions for lactose utilization and ethanol production were identified as 130 g/L of lactose at 42 °C in semi-synthetic media (SSM). Even though strain DSM 7239 showed the highest β-galactosidase activity of 27.8 ± 0.9 U mg−1, strains DSM 5422 and 5572 were identified as the best performing strains at shake flask experiments in terms of ethanol yield on the substrate, with 0.48 ± 0.03 g/g and 0.50 ± 0.03 g/g, respectively, after 1 day of fermentation.